Monitoring of precompetition affect in elite Italian archers during the World Championships - Robazza, C.; Bortoli, L.; Nougier, V. (International Journal of Sport Psychology, 2002)
Emotions were monitored in 13 archers (aged 18-40 yrs) of the Italian team prior to practice and competition. The purpose of the study was to test predictions derived from the Individual Zones of Optimal Functioning (IZOF) model extended to emotions other than anxiety. A central tenet of the IZOF model is that each performer has a specific optimal preperformance zone of idiosyncratic emotion intensities in which best performances will most likely occur if a performer's affect level lies outside their own optimal zone, performance will be impaired. An intrasubject, mixed nomothetic-idiographic approach was used to measure anxiety components (tension and worry), self-confidence, and idiosyncratic emotions. Current affect scores collected across seven assessments were contrasted with recalled optimal and poor performances. Results provided support for the IZOF model. Furthermore, deviations in prestart worry and self-confidence scores from recalled optimal performance scores were lower prior to successful performance than prior to less successful performance. Finally, successful performers compared to less successful counterparts reported less deviation scores from recalled optimal performance scores in prestart self-confidence across all assessments.